Optimalisasi Pendistribusian Dana Zakat Untuk Meningkatkan Kesejahteraan Masyarakat Ditinjau dari Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Nuraeni, Eni; Monaya, Nova; Rangkuti, Saddam Husein (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The Zakat institution is an institution that controls the source of zakat funds received from muzzaki and is also an institution that has the mission of distributing these funds to those entitled (mustahik). The development of the amil zakat system must be accompanied by a good and transparent public accountability process that prioritizes the motivation of the people in carrying out its mission. In oder for the implemention of zakat to unction properly, amil zakat institutions must apply the principles of good organizational governanc. The problems identified in this study are: (1) How to implement the trustworthiness of an amil in the distribution of zakat funds. (2) How to optimize the function of amil zakat institutions in the distribution of zakat funds for welfare in the perspective of trustworthiness. The method used is normative juridical. The result of this study is that in maintaining economic stability, good management is needed, in this case recomanded by the the Qur’an as amilin. The party is expected to be able to mediate professionally and seriously to manage, collect and distribute zakat funds. Channeled properly will realize welfare, zakat in its management must e managed by amil zakat who can hold the mandate of muzzaki so that these funds can be allocated to mustahik who need it by determining it according to islamic law. The nature of amanah and fathanah is important to be held byamil zakat where the nature of amanah is interpreted as a muslim’s life mission and fathanah is interpreted as a muslim’s life strategy, an amil is important in applying it is related to the trust of the people, meaning that muzzaki will wilingly sumbit their zakat through zakat management.